Perempuan Dalam Dunia Public Relations - Novi Kurnia; I Gusti Ngurah Putra (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2004)
Literature review shows that women gain more access to job in public relations. Observation in Yogyakarta shows that women are not easily top position in corporation due to understatement of the role of public relations in organizational structure. Discrimination against women is minimal except on family allowance.